2019
DOI: 10.1093/sleep/zsz143
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin+/nNOS+ neurons are involved in delta electroencephalogram activity and cortical-dependent recognition memory

Abstract: Slow-wave activity (SWA) is an oscillatory neocortical activity occurring in the electroencephalogram delta (δ) frequency range (~0.5–4 Hz) during nonrapid eye movement sleep. SWA is a reliable indicator of sleep homeostasis after acute sleep loss and is involved in memory processes. Evidence suggests that cortical neuronal nitric oxide synthase (nNOS) expressing neurons that coexpress somatostatin (SST) play a key role in regulating SWA. However, previous studies lacked selectivity in targeting specific types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Interestingly, these amygdalar nNOS GABAergic neurons were activated during sleep, an effect that may be linked to their serotonergic receptor expression, as 5-HT application changed their tonic firing to bursting mode measured in acute slices (Bocchio et al, 2016 ). In line with the potential role for nNOS/SST GABAergic neurons in controlling sleep, a recent study has shown that deleting nNOS from cortical SST inhibitory cells led to changes in slow wave sleep as well as in recognition memory (Zielinski et al, 2019 ). No doubt, specific modulation of the function of nNOS/NPY/SST GABAergic neurons using an intersectional viral strategy is needed in the future to uncover their contribution to sleep and other cortical operations.…”
Section: Gabaergic Projection Neuronsmentioning
confidence: 91%
“…Interestingly, these amygdalar nNOS GABAergic neurons were activated during sleep, an effect that may be linked to their serotonergic receptor expression, as 5-HT application changed their tonic firing to bursting mode measured in acute slices (Bocchio et al, 2016 ). In line with the potential role for nNOS/SST GABAergic neurons in controlling sleep, a recent study has shown that deleting nNOS from cortical SST inhibitory cells led to changes in slow wave sleep as well as in recognition memory (Zielinski et al, 2019 ). No doubt, specific modulation of the function of nNOS/NPY/SST GABAergic neurons using an intersectional viral strategy is needed in the future to uncover their contribution to sleep and other cortical operations.…”
Section: Gabaergic Projection Neuronsmentioning
confidence: 91%
“…We also showed that optogenetically evoked responses in nNOS-positive cells of the cerebral cortex are consistent with their role in slow-wave sleep physiology ( Gerashchenko et al, 2018 ). Furthermore, mice lacking nNOS expression in SST positive neurons exhibited significant impairments in both homeostatic low delta frequency range SWA production and a recognition memory task that relies on cortical input ( Zielinski et al, 2019 ). Further studies will determine whether activation of nNOS/somatostatin neurons in the cerebral cortex is efficient in reducing AD pathology, and whether this effect is mediated by SWA enhancement.…”
Section: Restoring Slow Wave Sleep Is a Promising Therapy For Admentioning
confidence: 99%
“…NREM, and particularly slow oscillations, have been implicated in the development of 43 cortical circuits, homeostatic regulation of network dynamics and memory consolidation [5][6][7][8][9][10] . 44 45 Neuronal nitric oxide (nNOS)-expressing neurons show elevated activity during sleep, as measured by the increased expression of the early gene cFos [11][12][13] , and may play a special role in controlling slow oscillations. Deep layer neurons of the cortex 3,4,14 , a variety of somato-dendritic 48 regenerative currents in cortical pyramidal cells and the excitatory recurrents among neurons have been postulated to be the source of stochastic metastability and persistent UP state activity 15 .…”
Section: Introductionmentioning
confidence: 99%